2020
DOI: 10.1038/s41598-020-65911-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome profiling of ex-vivo precision-cut slices from human pancreatic ductal adenocarcinoma

Abstract: Ex-vivo tumor tissue culture systems are used as models to test specific anti-cancer drugs. Their main advantage is that they are closely comparable with the in vivo tumor in their host organism. We previously reported that precision-cut organotypic tissue slices of pancreatic ductal adenocarcinoma (PDAC) can be successfully cultured ex-vivo for at least 4 days. In order to study how culturing might affect transcription patterns, we now performed genome-wide transcriptome profiling of both baseline (0 h) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
5
18
0
Order By: Relevance
“…Immunohistochemistry has been used to assess p53 status in PDAC and other cancers, as the mutated form of p53 protein is known to accumulate in the nucleus of tumour cells and is detectable by immunohistochemistry, whereas the wild-type protein is rapidly degraded 36 39 . Thus, by demonstrating positive p53 staining in tumour cells between day 0 and day 12 PDAC explants, and consistent with previous findings in ex vivo cultured PDAC slices 26 , our results suggest that tumour specific drivers such as p53 (which is mutated in approximately 75% of PDAC patients 40 , 41 ) are maintained in our PDAC explant model. Future studies will be required to examine the presence of other established PDAC tumour genetic drivers in our explant model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Immunohistochemistry has been used to assess p53 status in PDAC and other cancers, as the mutated form of p53 protein is known to accumulate in the nucleus of tumour cells and is detectable by immunohistochemistry, whereas the wild-type protein is rapidly degraded 36 39 . Thus, by demonstrating positive p53 staining in tumour cells between day 0 and day 12 PDAC explants, and consistent with previous findings in ex vivo cultured PDAC slices 26 , our results suggest that tumour specific drivers such as p53 (which is mutated in approximately 75% of PDAC patients 40 , 41 ) are maintained in our PDAC explant model. Future studies will be required to examine the presence of other established PDAC tumour genetic drivers in our explant model.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a study by Misra et al (2019) 25 cultured 350 μm thick PDAC tumour tissue-slices on a cell-culture Millicell insert for up to 96 h. While this was the first study to culture whole-tissue slices of PDAC and represents significant progress in developing more clinically relevant models of PDAC, the culture was only maintained for 96 h and low levels of tissue death were observed from as early as 24 h of culture 25 . A follow up study demonstrated that these cultured PDAC tissue slices have genomic stability with minimal transcriptome changes throughout the 72 h of culture 26 . Several other studies have developed in vitro co-culture models containing tumour cells, cancer-associated fibroblasts (CAFs), and endothelial cells [27][28][29][30][31] , but these models do not perfectly mimic the in situ complexity and heterogeneity of human PDAC tumours.…”
Section: Discussionmentioning
confidence: 99%
“…While this was the first study to culture whole-tissue slices of PDAC and represents significant progress in developing more clinically relevant models of PDAC, the culture was only maintained for 96 hours and increasing levels of tissue death were observed from as early as 24 hours of culture 24 . A follow up study demonstrated that these cultured PDAC tissue slices have genomic stability with minimal transcriptome changes throughout the 72 hours of culture 25 . Several other studies have developed in vitro co-culture models containing tumour cells, cancer-associated fibroblasts (CAFs), and endothelial cells 2630 , but these models do not perfectly mimic the in situ complexity and heterogeneity of human PDAC tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Several independent studies have now sought to bridge this gap using whole tumour tissue slices or tissue explants ex vivo ( Figure 2 ) [ 86 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Models That Reflect the Complex Microenvironment Are Required To Inform Functional Precision Medicine In Pdacmentioning
confidence: 99%
“…Misra et al [ 87 ] performed a more detailed characterisation of the ex vivo slice model, showing that slices can be maintained for 96 h with the presence of tumour cells, CAFs and immune cells. A follow-up study by the same team showed that the transcriptome of these slices is largely maintained throughout the culture [ 90 ]. Roife and colleagues [ 89 ] have since shown that drug sensitivity to gemcitabine and irinotecan in tissue slices from PDAC patient-derived xenograft models was consistent with patient response in the clinic, suggesting the model could potentially inform personalised therapy.…”
Section: Models That Reflect the Complex Microenvironment Are Required To Inform Functional Precision Medicine In Pdacmentioning
confidence: 99%